Effects of perinatal factors on sirtuin 3, 8-hydroxy-2'- deoxyguanosine, brain-derived neurotrophic factor and serotonin in cord blood and early breast milk: an observational study - Kata Nyárády; Réka Turai; Simone Funke; Erzsébet Györgyi; Alexandra Makai; Viktória Prémusz; József Bódis; Endre Sulyok (BMC, 2020)
Abstract Background The profile of sirtuin 3 (SIRT3), 8-hydroxy-2'-deoxyguanosine (8-OHdG), brain-derived neurotrophic factor (BDNF) and serotonin (5-HT) in cord blood and in early breast milk was studied and it was related to perinatal factors. 5-HT and BDNF signalling systems have been claimed to play a critical role in intrauterine development, postnatal adaptation and lactation. Since prematurity and Caesarean birth are frequently associated with inflammation and related oxidative stress, an attempt was made to reveal the adaptive changes of the protective SIRT3 and the complex interplay among these bioactive components in cord blood and early breast milk. Methods Three groups each consisting of 30 mothers were included in the study: mothers who underwent spontaneous vaginal birth at term (group I), Caesarean section at term (group II) and preterm birth (group III). Venous cord blood and early breast milk samples were collected for measuring the biomarkers. SIRT3, 8-OHdG, BDNF and 5-HT levels were determined by using commercially available ELISA kits. Results It was demonstrated that cord blood levels of SIRT3, BDNF and 5-HT were markedly reduced whereas those of 8-OHdG were significantly elevated after preterm birth when compared with birth at term. The Caesarean section was associated with a moderate decrease in BDNF and 5-HT, however, both SIRT3 and 8-OHdG remained unaffected. Breast milk levels of all biomarkers studied proved to be independent of their corresponding cord blood concentrations. In response to preterm birth breast milk SIRT3, 8-OHdG and 5-HT increased significantly, while a drastic fall occurred in BDNF. A significant positive relationship was found of 5-HT with SIRT3 and 8-OHdG irrespective of the gestational age and the mode of delivery. Conclusions It is suggested that the selected biomarkers in the breast milk mostly derive from local production by the mammary glands and 5-HT may have an essential role in the control of this process.